Characterization of Epoxy/Fe₂O₃ Nanocomposites with Enhanced Physical Properties - Sallal, Ali; M. Abdallh, Sarah; A. Nayef, Shahad (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
In this study, epoxy/iron oxide (EP/Fe₂O₃) nanocomposites were prepared at different weight percentages (0.1, 0.3, and 0.5 wt%) to investigate their structural, thermal, electrical, dielectric, and mechanical properties. Scanning electron microscopy (SEM) images showed that the Fe₂O₃ nanoparticles possessed a homogeneous morphology with irregular grain size and an average size of 60–70 nm, indicating their suitability for reinforcing polymer matrices. The addition of Fe₂O₃ nanoparticles significantly improved the thermal conductivity of the epoxy due to the formation of partial phonon transport pathways and enhanced interfacial interaction at higher addition percentages. Dielectric measurements showed an increase in the dielectric constant and dielectric loss with increasing Fe₂O₃ content, with both decreasing with increasing frequency due to interfacial polarization mechanisms. AC electrical conductivity results demonstrated frequency-dependent behavior with a marked improvement in conductivity upon nanoparticle addition. Furthermore, the Shore D hardness test results showed a gradual improvement with increasing Fe₂O₃ content, attributed to the restriction of epoxy chain movement and increased cross-linking density. These results confirm that Fe₂O₃ is an effective filler for enhancing the performance of multifunctional epoxy composites.